Interaction with a monoclonal antibody alters the expression of co-operativity by phenylalanine hydroxylase from rat liver. - Parniak, M A (1989)
Phenylalanine hydroxylase purified from rat liver shows positive co-operativity in response to variations in phenylalanine concentration when assayed with the naturally occurring cofactor tetrahydrobiopterin. In addition, preincubation of phenylalanine hydroxylase with phenylalanine results in a substantial activation of the tetrahydrobiopterin-dependent activity of the enzyme. The monoclonal antibody PH-1 binds to phenylalanine hydroxylase only after the enzyme has been preincubated with phenylalanine and is therefore assumed to recognize a conformational epitope associated with substrate-level activation of the hydroxylase. Under these conditions, PH-1 inhibits the activity of phenylalanine hydroxylase; however, at maximal binding of PH-1 the enzyme is still 2-3 fold activated relative to the native enzyme. The inhibition by PH-1 is non-competitive with respect to tetrahydropterin cofactor. This suggests that PH-1 does not bind to an epitope at the active site of the hydroxylase. Upon maximal binding of PH-1, the positive co-operativity normally expressed by phenylalanine hydroxylase with respect to variations in phenylalanine concentration is abolished. The monoclonal antibody may therefore interact with phenylalanine hydroxylase at or near the regulatory or activator-binding site for phenylalanine on the enzyme molecule.